REKONSTRUKSI PEMERIKSAAN PERKARA DI PENGADILAN HUBUNGAN INDUSTRIAL BERBASIS NILAI CEPAT, ADIL DAN MURAH - Hono Sejati (UNISSULA, 2016)
Judge’s decision should reflect the moral justice, social justice, and legal justice, the judge must hear the testimony of the parties, in order to produce a verdict worth of truth, honesty and has a value of fast, fair and cheap. In industrial disputes, the issue is how the dispute is resolved, in order to provide legal certainty based on values of justice for both workers and employers. Some issues examined in this study were (1) Why the Industrial Relations Court proceedings currently not fast, fair and cheap? (2) what barriers that happens in the proceedings in the Industrial Relations Court today that has not been fast, fair and cheap? How is the reconstruction proceedings in the Industrial Relations Court based the value of fast, fair and cheap? The research used sociological juridical approach. Data collection techniques were done by using interview, observation and documentation. Data were analyzed using interactive analysis method. Results of this study conclude that (1) Examination of the Industrial Relations Court has fast, fair, and inexpensive. It is caused by differences in terms of filing a lawsuit in which the provisions of civil law. In the case of filing a lawsuit on his nervous at the district court in the area where the defendant place residence or domicile (Article 118 HIR / Article 142 RBg, whereas in Article 81 of Law No. 2 of 2004 stipulates that industrial relations disputes lawsuit in the District Court jurisdiction covers the workers / laborers. From these provisions, no factor sequititrum forum rei is known to be abandoned. Forming the Act does not provide an explanation of the application of the principle of a lawsuit filed in the workers / laborers. (2) The obstacles that occur in examinations litigation industrial relations are: filing a lawsuit, calling longer because the place stay defendant outside the jurisdiction of the courts located or the defendant has died, the company that has no operations or directors have left Indonesia, as well as the lack of control of the board Unions / Labour as the holder of the power which is actually not a graduate or undergraduate law will hinder the investigation because the process examination the judge must be active members of the advice and knowledge of proceedings. (3) Reconstruction of the court proceedings in industrial relations is based on the value of fast, fair, and inexpensive which is done by consensus as the settlement of disputes in the Industrial Relations Court.